Chemical and rheological investigation on the short- and long-term aging properties of bio-binders for road pavements. (30th August 2019) - Ingrassia, Lorenzo Paolo; Lu, Xiaohu; Ferrotti, Gilda; Canestrari, Francesco
Highlights: The bio-oil inhibits the formation of carbonyl compounds at 1700 cm −1 during aging. The bio-oil reduces the aromaticity of the binders. Bio-binders' performance at intermediate and high temperatures is satisfactory. Bio-binders show similar or even higher aging resistance than conventional bitumens. There is a direct link between chemical and rheological changes induced by aging. Abstract: In recent years, due to growing environmental concerns, sustainability and circular economy have become two issues of crucial importance. In road engineering, in order to pursue such principles, one of the main current trends is to employ industrial residues and by-products deriving from renewable materials in partial substitution of petroleum-based bitumen. However, uncertainty on the durability and long-term performance of such materials still exists. In this regard, this paper focuses on the short- and long-term aging properties of bio-binders obtained by partially replacing a 50/70 bitumen with different percentages of a renewable bio-oil generated as a by-product by the wood and paper industries. The experimental investigation carried out includes conventional tests, chemical analyses as well as rheological testing and modelling with 2S2P1D model. Conventional bitumens were also tested for comparison purposes. The main chemical results indicate that, despite a small amount of additional oxidized compounds related to esters, the bio-oil addition significantly inhibits the formation of carbonyl compounds and reduces the aromaticity of the binders. In terms of performance-related properties, the permanent deformation resistance and the fatigue resistance of these bio-binders are generally comparable to those of traditional bitumens having similar penetration grade, without any specific drawback. Moreover, a linear material-dependent relationship was found between chemical and rheological changes induced by aging as well as the chemical and rheological parameters most strictly related to the binders' oxidation were identified and considered as aging indicators. Based on the evolution of these parameters, the bio-binders investigated in this study may have comparable or even better aging resistance with respect to conventional bitumens with similar penetration grade. Therefore, such bio-binders can be considered an effective sustainable alternative to traditional bituminous binders.